Energy and exergy analysis of an HVAC system - Quintanilla Muñoz, Alberto Martin (Pontificia Universidad Católica del Perú, 2017)
The efficient use of energy is a major issue nowadays. Environmental and economic purposes push various investigations to focus on the performances of energy systems and equipment. In the context of the coming energy transition, Heat, Ventilation and Air Conditioning (HVAC) systems will certainly take an increasing and worldwide importance. In this work, energy and exergy analysis are used to assess the performances of each component of an air treatment station. Results of energy and exergy analysis for each process are presented. The most important result is that simple heating and cooling processes with deshumidification have the worst exergy efficiencies; and that both processes represent almost all the exergy losses of the studied HVAC system.
Keywords: Energía eólica; Consumo de energía; https://purl.org/pe-repo/ocde/ford#2.00.00